The Experiment of Floating Ability of Material of Polyurethane and Styrofoam - Indradi Setiyanto; Agus Hartoko (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
Polyurethane can  be used  as alternative of  substituted material  of  synthetic cork (Styrofoam)  giving buoyancy at float vest. The research was aimed to observe the difference both materials (Polyurethane and cork) on acceptable load, so that efficiency can be estimated. The same load was given to gravity at both material that is 234.576 g, then checked the float ability. Results showed that Polyurethane indicated buoyancy of polyurethane better cork, with efficiency 3.6 %, for sample material with size of 10 cm x 7.5 cm x 5.5 cm. The Significant change of efficiency was expected can be done by determination of material (sample)  according  to  use in  field  and  different  density  of  polyurethane  when  conducting  moldings process.   Key words: The experiment of floating ability